The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1995
DOI: 10.1002/j.1460-2075.1995.tb00207.x
|View full text |Cite
|
Sign up to set email alerts
|

A synthetic, chemically modified ribozyme eliminates amelogenin, the major translation product in developing mouse enamel in vivo.

Abstract: Ribozymes are small RNA structures capable of cleaving RNA target molecules in a catalytic fashion. Designed ribozymes can be targeted to specific mRNAs, blocking their expression without affecting normal functions of other genes. Because of their specific and catalytic mode of action ribozymes are ideal agents for therapeutic interventions against malfunctioning or foreign gene products. Here we report successful experiments to ‘knock out’ a major translation product in vivo using synthesized, chemically modi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
66
0
1

Year Published

1996
1996
2007
2007

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(71 citation statements)
references
References 30 publications
4
66
0
1
Order By: Relevance
“…2A, lanes 1-5) or p70 (Fig. 2B, lanes [1][2][3][4][5], whereas Msx2FL by itself was a potent transcriptional repressor. On the other hand, C/EBP␣ was capable of overcoming the repressive effect of Msx2FL on the reporter construct p2207 (Fig.…”
Section: C/ebp␣ and Msx2 Antagonized Each Other In Regulating Mousementioning
confidence: 99%
See 1 more Smart Citation
“…2A, lanes 1-5) or p70 (Fig. 2B, lanes [1][2][3][4][5], whereas Msx2FL by itself was a potent transcriptional repressor. On the other hand, C/EBP␣ was capable of overcoming the repressive effect of Msx2FL on the reporter construct p2207 (Fig.…”
Section: C/ebp␣ and Msx2 Antagonized Each Other In Regulating Mousementioning
confidence: 99%
“…Several mutations in the human Xchromosomal amelogenin gene have been identified from patients with the inherited enamel defect X-linked Amelogenesis imperfecta (1)(2)(3). Disruption of amelogenin synthesis during tooth development with either antisense oligonucleotides or ribozymes results in disorganized enamel (4,5). Amelogenin expression is ameloblast specific and developmentally regulated at the temporal and spatial level (6 -13).…”
mentioning
confidence: 99%
“…Amelogenin is unique in that it self-assembles into nanospheres, supra-molecular structures observed in vitro [6][7][8] and in vivo [7,9] which are believed to be critical to the function of the protein. Several in vivo studies using antisense mice [10], knock out mice [11], transgenic mice [12], and hammerhead ribozymes [13] have investigated the role of amelogenin in regulating enamel nucleation and growth. These studies have shown reduced mineralization in the absence of amelogenin or when amelogenin mutants did not form nanospheres.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive modification of the hammerhead ribozyme motif can give dramatic enhancement of the ribozyme half-life in biological fluids (8,13). Modifications of this type have been demonstrated to give efficacy in cell culture (7) and in vivo (13,14).We have previously described dose-dependent inhibition of smooth muscle cell proliferation by select ribozymes targeting c-myb. Little inhibition was observed with catalytically inactive control RNA molecules.…”
mentioning
confidence: 99%